1997
DOI: 10.1046/j.1365-2141.1997.d01-2067.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibody‐dependent C5b‐9 formation

Abstract: The relationship between the presence of antiphospholipid antibodies (APA) and the production of the terminal membrane attack complex (MAC) of complement (C5b‐9) was studied. Serum samples from known high positive APA patients induced platelet activation and destruction which was inhibited by heat‐inactivation of the sera. The response was restored if the heat‐inactivated APA‐positive sera were supplemented with normal sera. Adsorption of the APA‐positive sera with phospholipid (PL)‐coated polystyrene beads in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…It was shown in mouse models that the inhibitory effect of heparin on aPL-induced foetal loss was because of inhibition of the complement system and not because of inhibition of thrombin formation [53][54][55]. Additional experiments with deficient mice have linked C3, C5 and the membrane attack complex to foetal loss and thrombosis, probably by increasing tissue factor expression on different cells [56].…”
mentioning
confidence: 99%
“…It was shown in mouse models that the inhibitory effect of heparin on aPL-induced foetal loss was because of inhibition of the complement system and not because of inhibition of thrombin formation [53][54][55]. Additional experiments with deficient mice have linked C3, C5 and the membrane attack complex to foetal loss and thrombosis, probably by increasing tissue factor expression on different cells [56].…”
mentioning
confidence: 99%
“…Complement C4d bound to platelets is found in 18% of lupus patients but is highly associated with the lupus anticoagulant (50%, P < 0.0001) and aCL (P < 0.05), perhaps representing an important cellular target of aPL-mediated damage [8]. This finding is of interest, because earlier research showed that serum from patients with high-titer aPL could induce platelet activation and destruction, and this activity was destroyed by heat inactivation or the addition of monoclonal antibodies to C5b-9 [9].…”
Section: Observations In People With Antiphospholipid Syndromementioning
confidence: 81%
“…Antiphospholipid antibodies are known to bind to platelet membrane structures [14,[28][29][30][31][32], which may result in thrombocytopenia or hemostatic activation [14]. In addition, an association between aPL antibodies and immunemediated thrombocytopenia (ITP) has been established [28].…”
Section: Platelets As Phospholipid Templates and Regulators Of Hemostmentioning
confidence: 99%